Understanding global slavery : a reader - Bales, Kevin (University of California Press, 2005)
Slavery continues as a blight on the human world, with an estimated 27 million people around the world in bondage. Kevin Bales undertakes a discussion of the causes of enslavement & the socio-economic factors that sustain slavery in the 21st century.